Titanium dioxide nanotubes incorporated into conventional glass ionomer cement alter the biological behavior of pre-odontoblastic cells - Meyer, Maria Davoli; Coelho, Rogério Meneses Ibiapina; Rangel-Coelho, João Pedro; Costa, Bruna Carolina [UNESP]; Teixeira, Lucas Novaes; Martinez, Elizabeth Ferreira; Casarin, Renato Corrêa Viana; Santamaria, Mauro Pedrine; França, Fabiana Mantovani Gomes; Nociti-Jr, Francisco Humberto; Lisboa-Filho, Paulo Noronha [UNESP]; Kantovitz, Kamila Rosamilia (Elsevier, 2025)
The objective was to address the repercussion of adding titanium dioxide nanotubes (TiO2-nt) into high-viscosity conventional glass ionomer cement (GIC) on the biological properties of pre-odontoblastic cells (MDPC-23) challenged by lipopolysaccharides (LPS - 2 μg/mL). TiO2-nt was added to Ketac Molar EasyMix at 3, 5, 7 %, whereas unblended GIC served as control. Analyses included proliferation (n=6; 24, 48, 72 h), metabolism (MTT; n=6; 24, 48, 72 h); morphology laser microscopy (n=3; 24, 48, 72 h); proteome assessments IL-1β, IL-6, IL-10, VEGF, TNF-α (n=3; 12, 18 h); mRNA levels (RT-PCR) of Il-1β, Il-6, Il-10, VEGF, TNF-α (n=3; 12, 18 h) and DSPP (n=3; 24, 72, 120 h). Data analysis included Shapiro-Wilk, Levene, and generalized linear models (α=0.05). Results demonstrated that cell proliferation increased over time for all groups, and was not impacted by TiO2-nt (p>0.05). GIC groups displayed lower MTT values compared to cells cultured without GIC discs (p=0.019); disregarding the presence of TiO2. Remarkably, TiO2-nt reversed the effect of GIC, reducing the levels of selected biomarkers. LPS treatment modified the expression of the immune-inflammatory markers by MDPC-23 cells (p<0.0001). Morphological analysis did not reveal distinctions for any of the studied. TiO2-nt modulated immune-inflammatory and dentin marker expression by MDPC-23 cells cultured on conventional GIC discs, and did not affect cell morphology/viability, regardless LPS exposure. In conclusion, TiO2-nt may become a reliable clinical strategy to encourage pulp tissue repair.
Keywords: Dental Restoration; Glass Ionomer Cements; Odontoblasts; Pulp